Annealing effect on tunneling magnetoresistance in MgO-based magnetic tunnel junctions with FeMn exchange-bias layer - COEY, JOHN MICHAEL DAVID; FENG, JIA-FENG (My University, 2010)
MgO-based magnetic tunnel junctions were fabricated, with a thin pinned CoFeB layer in the unbalanced synthetic antiferromagnet part of the stack FeMn/CoFe/Ru/CoFeB. Inverted and normal tunneling magnetoresistance (TMR) values occur at low and high annealing temperatures (Ta), respectively. The TMR ratio remains inverted up to Ta=300 ?C and it becomes normal around Ta=350 ?C. The exchange bias of FeMn disappears at high Ta. The sign reversal of the TMR ratio is mainly attributed to the disappearance of the exchange bias due to manganese diffusion during the annealing process.
PUBLISHED
Keywords: Magnetic tunnel junctions (MTJs); Inverted and normal tunneling magnetoresistance (TMR); Elemental diffusion